Criterion and Divergent Validity of the Sexual Minority Adolescent Stress Inventory - Goldbach, Jeremy T.; Schrager, Sheree M.; Mamey, Mary R. (Frontiers in Psychology, 2017)
Sexual minority adolescents (SMA) consistently report health disparities compared to their heterosexual counterparts, yet the underlying mechanisms of these negative health outcomes remain unclear. The predominant explanatory model is the minority stress theory; however, this model was developed largely with adults, and no valid and comprehensive measure of minority stress has been developed for adolescents. The present study validated a newly developed instrument to measure minority stress among racially and ethnically diverse SMA. A sample of 346 SMA aged 14–17 was recruited and surveyed between February 2015 and July 2016. The focal measure of interest was the 64-item, 11-factor Sexual Minority Adolescent Stress Inventory (SMASI) developed in the initial phase of this study. Criterion validation measures included measures of depressive symptoms, suicidality and self-harm, youth problem behaviors, and substance use; the general Adolescent Stress Questionnaire (ASQ) was included as a measure of divergent validity. Analyses included Pearson and tetrachoric correlations to establish criterion and divergent validity and structural equation modeling to assess the explanatory utility of the SMASI relative to the ASQ. SMASI scores were significantly associated with all outcomes but only moderately associated with the ASQ (r = -.13 to .51). Analyses revealed significant associations of a latent minority stress variable with both proximal and distal health outcomes beyond the variation explained by general stress. Results show that the SMASI is the first instrument to validly measure minority stress among SMA.